Hubungan Jumlah Obat yang Digunakan terhadap Risiko Terjadinya Drug-Related Problems pada Pasien Asma Di Suatu Rumah Sakit Di Surabaya - Amelia Lorensia; Rizka I Wijaya (Journal of Tropical Pharmacy and Chemistry, 2016)
Asthma is a chronic inflammatory disorder of the respiratory tract are at risk of polypharmacy, which is associated with an increased risk of drug-related problems (DRPs) and adverse clinical outcomes. This study aimed to analyze the relationship between the amount of drug used with the incidence of DRPs in hospitalized asthma patients. Research were using retrospective methods, by analyzing the medical records of patients undergoing asthma hospitalizations for 2 years. The number of patients analyzed was 60 people. Results of research conducted by the Spearman test for non-parametric tests, show that there is a correlation between the amount of drug to the type of drugs that are less precise DRPs (p <0.05), so that more and more types of drugs used by patients with asthma, the greater the risk of patients getting the drug less appropriate. Therefore it takes the role of pharmacists in monitoring and recommending rational drug for asthma patients who underwent inpatient in a hospital, for treatment obtained by the patient effective and optimal.